A review on the ecological quality status assessment in aquatic systems using community based indicators and ecotoxicological tools: what might be the added value of their combination?. (January 2015) - Martinez-Haro, Monica; Beiras, Ricardo; Bellas, Juan; Capela, Ricardo; Coelho, João Pedro; Lopes, Isabel; Moreira-Santos, Matilde; Reis-Henriques, Armanda Maria; Ribeiro, Rui; Santos, M. Miguel; Marques, João Carlos
Abstract: The European Water Framework Directive (WFD) represents a transformation of the guidelines for water quality assessment and monitoring across all EU Member States. At present, it is widely accepted that the WFD requires holistic and multidisciplinary ecological approaches by integrating multiple lines of evidence. Within the scope of the WFD, the scientific community identified clear opportunities to take advantage of an ecotoxicological line of evidence. In this context, ecotoxicological tools, namely biomarkers and bioassays, were proposed to contribute to the integration of the chemical and biological indicators, and thus to provide an overall insight into the quality of a water body. More than one decade after the publication of the WFD, we reviewed the studies that have attempted to integrate ecotoxicological tools in the assessment of surface water bodies. For this purpose, we reviewed studies providing an ecological water status assessment through more conventional community based approaches, in which biomarkers and/or bioassays were also applied to complement the evaluation. Overall, from our review emerges that studies at community level appear suitable for assessing the ecological quality of water bodies, whereas the bioassays/biomarkers are especially useful as early warning systems and to investigate the causes of ecological impairment, allowing a better understanding of the cause–effect-relationships. In this sense, community level responses and biomarkers/bioassays seem to be clearly complementary, reinforcing the need of combining the approaches of different disciplines to achieve the best evaluation of ecosystem communities' health.